“SEASONAL” PROPAGANDA COMMUNICATION ON THE POLITICAL STAGE - Siahaan, Chontina; Adrian, Donal (Sociae Polites, 2024)
Facing the general election in 2024 in all provinces in Indonesia, quite a lot of propaganda communication has been found by legislative candidates to attract the attention of the public to be able to elect them as potential leaders for the next 5 years. This research uses qualitative methods with data collection techniques consisting of observation, in-depth interviews, and documentation. 10 informants were registered as legislative candidates. Data analysis uses data reduction, data display, and conclusion/verification. The research results show that ahead of the 2024 General Election, executive and legislative candidates are taking various methods to get the attention and voting rights of the people based on their electoral districts and Indonesia in general. It was found that the seasonal propaganda carried out by the candidates started from explaining the superiority of themselves and their party, making political promises, providing educational assistance and basic needs assistance, but with the sentence that if I were then this assistance would continue to be implemented. Furthermore, visiting people in need such as those who are sick, holding sports competitions, arts, and so on. What is also worrying is bringing down the good name of the opposing party and using issues of ethnicity, religion, race, and inter-group issues which are conveyed in direct communication and the media.